Neuronal nitric oxide synthase expressing neurons: a journey from birth to neuronal circuits - Tricoire, Ludovic; Tania, Vitalis (Frontiers in Neural Circuits, 2012)
Nitric oxide (NO) is an important signaling molecule crucial for many physiological processes such as synaptic plasticity, vasomotricity and inflammation. Neuronal nitric oxide synthase (nNOS) is the enzyme responsible for the synthesis of NO by neurons. In the juvenile and mature hippocampus and neocortex nNOS is primarily expressed by subpopulations of GABAergic interneurons. Over the past two decades, many advances have been achieved in the characterization of neocortical and hippocampal nNOS expressing neurons. In this review, we summarize past and present studies that have characterized the electrophysiological, morphological, molecular and synaptic properties of these neurons. We also discuss recent studies that have shed light on the developmental origins and specification of GABAergic neurons with specific attention to neocortical and hippocampal nNOS expressing GABAergic neurons. Finally, we summarize the roles of NO and nNOS-expressing inhibitory neurons.